Jelly petrolatum conjunctival granuloma: a case report - Carlos E. Pavésio (Arquivos Brasileiros de Oftalmologia)
SUMMARY The authors report a case of a conjunctival granuloma occurring as a complication of a paranasal sinus procedure. Bilateral fractures of the ethimoid bones allowed the subconjunctival infiltration of the jelly petrolatum commonly used at the end of these procedures.